2009
DOI: 10.1029/2008jb006240
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on continued episodic inflation at Long Valley Caldera, based on seismic and geodetic observations

Abstract: Long Valley Caldera, a large and potentially explosive silicic system, has experienced highly anomalous continued inflation since late 1970s. We characterize an episode of rapid episodic uplift occurring between 2002 and 2003 following similar episodes of 1979–1980, 1983, 1989–1990, and 1997–1998. This most recent episode was the first to be observed by a dense array of 13 continuous Global Positioning System (GPS) stations. Similar to previously observed episodes of deformation, uplift is quasi‐radially symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 64 publications
1
41
0
2
Order By: Relevance
“…[13] As seen in other active silicic calderas, including Long Valley [Newman et al, 2006;Feng and Newman, 2009] and Yellowstone [Chang et al, 2007], and the recently erupting Eyjafjallajökull stratovolcano [Sigmundsson et al, 2010], the temporal occurrence of seismicity mimics observed deformation (Figure 1). Each change in the cumulative seismicity marks a similar change in the rate of deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] As seen in other active silicic calderas, including Long Valley [Newman et al, 2006;Feng and Newman, 2009] and Yellowstone [Chang et al, 2007], and the recently erupting Eyjafjallajökull stratovolcano [Sigmundsson et al, 2010], the temporal occurrence of seismicity mimics observed deformation (Figure 1). Each change in the cumulative seismicity marks a similar change in the rate of deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Such a model requires only the assumption that a small spherical source is radially expanding in a homogeneous elastic Poisson half-space. Following an iterative grid search method used by Feng and Newman [2009], we use an apriori estimate of DV and depth z to initially constrain a preferred horizontal position. Using this position a new best fit z and DV is determined, which are again used as input for a repeated grid search to refine the location and DV for improved final solutions.…”
Section: Modelsmentioning
confidence: 99%
“…Previous studies on the 1997-1998, 2002-2003 uplift events indicate that the intrusion beneath the resurgent dome may be cigar-shaped [e.g., 10,11,12,13]. So we assume the most recent deformation episodes since 2000 are caused similarly by a finite ellipsoidal source.…”
Section: Model Methodsmentioning
confidence: 97%
“…This may seem peculiar, if not paradoxal, at least for the cases of geodetic data describing geophysical models; for instance modeling seismic faults from comparison of preand post-seismic geodetic observations [5,8,12] and modeling of magma sources in volcanoes from comparison of GPS or INSAR data from different campaigns [4,11].…”
Section: Introductionmentioning
confidence: 97%